Assessment on Alternative Health Care Modalities: A Basis for Health Training and Development - Ocampo, Divina B.; Flores, Emily A.; Mallari, Cheena B.; Manuel, Mark Denver V. (Proceedings Series on Health & Medical Sciences, 2025)
World Health Organization (WHO) described traditional medicine as a health practice with strong historical and cultural roots, which has global acceptability and applicability. It is an important and often underestimated health resource with many applications, especially in the prevention and management of lifestyle-related chronic diseases. This research assessed the knowledge, skills and attitude on the alternative health care modalities of the resident of Poblacion West, General Tinio, Cabanatuan City, Philippines. The researchers used a quantitative descriptive correlational research method and a purposive sampling technique to examine the data from the respondents. A self-made questionnaire survey form was used to face-to-face collect data from the respondents. The research showed that most of the barangay health workers were female and do not have enough knowledge and skills to perform reflexology, acupressure, chiropractics, and nutritional therapy, but the respondents showed interest to learn more despite the fact that they have limited knowledge and skills about these modalities. Results were presented to the Barangay Health Workers (BHW)’s and heads to address the result of the study and possibly be the basis of health programs and development to aid respondents’ gaps in their knowledge and practices of traditional healthcare modalities.